Traffic Safety Factors in the Qassim Region of Saudi Arabia - Ahmad A. Al-Tit; Imed Ben Dhaou; Fahad M. Albejaidi; Mohammed S. Alshitawi (SAGE Open, 2020)
This study investigates the factors that affect traffic safety in the Qassim region. A questionnaire was developed on the basis of the Handbook of road safety and consisted of 85 items measuring seven dimensions: area-wide traffic calming (22 items), vehicle design and protective devices (26 items), road design (24 items), road maintenance (three items), traffic education (four items), police campaigns and sanctions (three items), and post-accident care (three items). A sample encompassing 1,500 Qassim University students, and visitors was randomly selected to collect data. A total of 1,500 questionnaires were distributed to students, and visitors of which 1,053 were retrieved. The elimination of data outliers resulted in a sample of 909 subjects. The results pointed out a moderate level of traffic safety in the Qassim region. Furthermore, 10 leading causes of road traffic accidents emerged, namely, excess speed, irregular bypasses, irregular rotations, lack of prioritization of other drivers, irregular stops, lack of road readiness, driver carelessness, use of a mobile phone while driving, noncompliance with traffic signals, and, finally, nonuse of seat belts. On the basis of these results, conclusions and policy implications were provided.